An overview on oxidation of metallic interconnects in solid oxide fuel cells under various atmospheres - Yang, Gongmei; Potter, Andrew; Sumner, Joy (Elsevier, 2025)
This study explores the emergence of oxidation-resistant alloys as potential replacements for traditional ceramics in Solid Oxide Fuel Cells (SOFCs), specifically Ferritic Stainless Steel (FFS). Despite its promise, FFS encounters challenges such as oxidation and corrosion. Most research on FFS interconnect damage has primarily focused on high-temperature oxidation in single atmospheres. However, in practice, the interconnect is exposed to both oxidizing and reducing atmospheres concurrently, leading to enhanced oxidation known as the dual atmosphere effect. The significance of this phenomenon is increasingly recognized by researchers and industry experts, yet understanding its implications for FFS degradation and protective measures remains a young discipline. This article provides an overview of the oxidation mechanisms of FSS under various conditions, proposed mechanisms, and potential protective strategies to address the effects of the dual atmosphere.
Keywords: 40 Engineering; 4016 Materials Engineering; Energy; 34 Chemical sciences; Solid oxide fuel cells; Dual atmosphere; Oxidation; Corrosion; Coating